Codependence and emotional intelligence in women students from a private university in Lima - Silva Cruz, Segundo Julio (2020)
The purpose of this study was to determine the relationship between codependence and emotional intelligence in female students of a private university in Metropolitan Lima. The design of the investigation was a correlational descriptive study. The study population consisted of 405 female students, with an average age between 18 and 25 years.The Kappa statistic showed a significant agreement value of .8409. In addition, a pilot study was conducted with 40 participants, and obtained a Cronbach’s Alpha Indicator of .85, which matches with the instrument author’s results. Bar-On Emotional Quotient Inventory (EQ-i) was created by BarOn (1977). For the Peruvian sample, the reliability of Cronbach’s Alpha Coefficient for the total inventory is very high: .93; for the EQ-i components, this coefficient results are among.77 and .91. These data was validated in Lima by Ugarriza (2001). The current study is a non-probabilistic and intentional sampling method, with a sample of 203 female university students. The results showed a negative relationship between codependence and emotional intelligence in female students with a Spearman’s Correlation Coefficient of -.291**, which is significant at .01. Similar data was found in other investigations.